THE INFLUENCE OF MACROECONOMIC INDICATORS OF UKRAINE ON THE FORMATION OF VOLUME OF INSURANCE PAYMENTS BY INSURANCE COMPANIES - Shyshpanova, Natalia; Khorenzhenko, Valeriia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
Abstract. The article deals with the relationship of insurance payments volumes with macroeconomic indicators. The classification of insurance payments according to different features (purpose of contribution, type of risks, form of payment of insurance premiums, term of payment, method of calculation) is given. It is established that the receipt of insurance payments depends on the influence of both internal and external factors. The main indicators of activity of the insurance market of Ukraine are analyzed. The dynamics of insurance payments of insurance companies of Ukraine and the dynamics of Ukraine's GDP in dollar terms and in national currency are presented. The dynamics of insurance payments receipts over the period under review are volatile, and are largely similar to the dynamics of nominal GDP, both in national currency and in dollar terms. However, it has been found that there is a prevailing increase in insurance payments. It is revealed that the insurance market is expanding its capacity and gradually developing. The correlation-regression analysis of the dependence of changes in the volume of insurance payments on the level of GDP is carried out. It is established that the amount of insurance payments depends on the level of GDP in the country and that the econometric model can be considered adequate to the actual experimental data and to carry out economic analysis on the basis of the adopted model. It is revealed that despite the rather high growth rates of quantitative indicators, the institutional and functional characteristics of the Ukrainian insurance market generally do not correspond to the trends of the world insurance markets and the real needs of the domestic economy, which causes its significant lag in the global process of formation of the world financial system. It is determined that for further development and capacity building of Ukrainian insurance companies it is advisable to create conditions for sustainable growth of the Ukrainian insurance sector. On the basis of the conducted researches, recommendations on formation of volumes of insurance payments of insurance companies of Ukraine are offered. It is substantiated that the increase of economic development, creation of preconditions for improvement of the level and quality of life of the population, increase of its incomes and solvency, is crucial for activating the development of the insurance market of Ukraine.